Proton irradiation-decelerated intergranular corrosion of Ni-Cr alloys in molten salt - Weiyue Zhou (Nature Portfolio, 2020)
Better understanding the synergy between radiation and corrosion is necessary to deploy advanced nuclear reactors. Here, the authors contradict the misconception that radiation always results in deleterious effects and show that proton irradiation slows the corrosion of Ni-Cr alloys in 650 °C molten salt.